Implementasi Sistem Merit dalam Rekrutmen ASN di Kabupaten Kampar - lisa nurmaya; Rury Febrina (Journal of Governance Innovation, 2021)
ASN recruitment is important in recruiting employees  needed in running the organization. Recruitment or placement of employees according to the merit system is the placement of the best people to occupy the positions needed because of the quality and capacity they control. As for the purpose of the implementation of this study, namely to understand the application of ASN recruitment in Kampar District. As for the research method used in this research is descriptive research. The conclusions obtained from this study are indicators of implementation of merit system rules which are related to the implementation of recruitment, namely: 1) organized and orderly planning carried out throughcreative and innovative recruitment techniques, 2) each participant selection candidate must have a responsibility and be well explained, 3) the implementation of the recruitment system links participants who have the ability and become an appropriate source in the implementation of the survey to be ableaccommodating all people from various groups, 4) each candidate for selection is given fair treatment regardless of their background from which race 5) recruitment is carried out on knowledge, ability and expertise based on open and fair competition for everyone forget equal opportunities available, 6) the implementation of procedures for selection can be carried out in order to confirm that candidates have the ability and the right to get a position in the right job according to their abilities, 7) staff who are accepted should be protected from various special attitudesbecause of something or the attitude of deception for political purposes.   Rekrutmen ASN adalah hal penting dalam pengadaan pegawai sesuai kebutuhan di dalam menjalankan organisasi. Rekrutmen atau penempatan pegawai menurut sistem merit merupakan penempatan orang-orang terbaik untuk menempati jabatan yang diperlukan karena kualitas dan kapasitas  yang dikuasainya. Adapun tujuan pelaksanaan Penelitian ini yaitu untuk memahami penerapan rekrutmen ASN yang berada dalam Kabupaten Kampar. Adapun metode penelitian yang digunakan dalam penelitian ini yaitu penelitian deskriptif. Kesimpulan yang diperoleh dari penelitian ini adalah  Indikator pelaksanaan aturan merit sistem dimana terkait dengan pelaksaaan  rekrutmen  yaitu: 1) perencanaan yang tertata dan teratur yang dilakukan melalui teknik rekrut merekrut yang kreatif dan inovatif, 2) setiap calon seleksi ikut berperan serta harus memiliki tanggung jawab dan dijelaskan dengan baik, 3) pelaksanaan sistem rekrutmen mengaitkan peserta yang memiliki kemampuan dan menjadi sumber yang sesuai dalam pelaksanaan rekrumet agar mampu menampung semua masyarakat dari berbagai golongan, 4) setap calon seleksi diberi perlakuan yang adil tidak memedulikan latar belakang dia dari ras mana 5) rekrutmen dilaksanakan pada pengetahuan, kemampuan dan keahlian berdasarkan persaingan yang terbuka dan adil terhadap segala orang untuk mendapatkan kesetaraan pada kesempatan yang ada, 6) pelaksanaan prosedur pada seleksi dapat dilaksanakan guna menegaskan calon  yang memiliki kemampuan dan tepat dalam memperoleh posisi di pekerjaan yang tepat sesuai kemampuannya, 7) staf yang diterima patut terlindungi dari berbagai sikap spesial karena suatu hal atau adanya sikap pembohongan untuk tujuan perpolitikan.